Réponses

  • Utilisateur Brainly
2013-06-03T13:51:05+02:00

(1+x)^(1/x)=exp(ln(1+x)/x)

 

le développement limité de ln(1+x) à l'ordre 2 est :

ln(1+x)=x-x²/2+o(x²)

 

donc ln(1+x)/x=1-x/2+o(x)

donc exp(ln(1+x)/x)=exp(1-x/2+o(x))=exp(1)/(exp(x/2+o(x))

 

de plus : exp(u)=1+u+u²/2+o(u²)

donc en posant u=x/2

exp(x/2)=1+x/2+x²/4+o(x²)

 

donc exp(ln(1+x)/x)=e/(1+x/2+x²/4+o(x²))

 

enfin 1/(1+h)=1-h+h²+o(h²)

en posant h=x/2+x²/4

1/(1+x/2)=1-(x/2+x²/4)+x²/4+o(x²)

                =1-x/2+o(x²)

 

ainsi : exp(ln(1+x)/x)=e(1-x/2+o(x²))

soit (1+x)^(1/x)=e-ex/2+o(x²)

 

rque : la limite de (1+x)^(1/x) quand x tend vers 0 est e=exp(1) ≈ 2,718